1995
DOI: 10.1080/01932699508943659
|View full text |Cite
|
Sign up to set email alerts
|

Phase Equilibria and Evaporation Rates in a Four Component Emulsion

Abstract: The cosmetic system ofwater, lecithin,polyethylene glycol (M.W. 5000), and white oil was studied and the phase diagram determined using visual observation, low angle x-ray diffraction and chemical analysis.The results showed the lecithinI water lamellarliquid crystal to be retained when the polyethylene glycol was gradually replaced by white oil. The polyethylene glycol was solubilizedin the lamellarliquid'crystal to a maximum level of 10%, the white oil to 8%.The evaporation rate, from a thinlayer, was follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 4 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…Beyond the advantages already mentioned, in a research conducted by Moaddel and Friberg (1995), the authors showed that the presence of lamellar liquid crystals in an emulsion avoids the water evaporation rate in this system, thus contributing in another way to the stability and maintenance of the cosmetic quality.…”
Section: Small Angle X-ray Scattering (Saxs)mentioning
confidence: 99%
“…Beyond the advantages already mentioned, in a research conducted by Moaddel and Friberg (1995), the authors showed that the presence of lamellar liquid crystals in an emulsion avoids the water evaporation rate in this system, thus contributing in another way to the stability and maintenance of the cosmetic quality.…”
Section: Small Angle X-ray Scattering (Saxs)mentioning
confidence: 99%
“…3 It has been shown that PEO can be adsorbed on many kinds of particle surfaces such as mica, [4][5][6] glass, 7,8 latex, [9][10][11][12][13][14][15][16] silica, 6,13,[17][18][19][20][21] and the air-water interface. 22 It can interact with neutral lipid 23 and oil 24 surfaces. Numerous experimental techniques have characterized the adsorbed PEO conformations at the above interfaces.…”
Section: Introductionmentioning
confidence: 99%